(untitled) (Journal of Computational Mathematics, 2007)
In magnetoencephalography (MEG) a primary current is activated within a bounded conductive medium, i.e., the head. The primary current excites an induction current and the total (primary plus induction) current generates a magnetic field which, outside the conductor, is irrotational and solenoidal. Consequently, the exterior magnetic field can be expressed as the gradient of a harmonic function, known as the magnetic potential. We show that for the case of a triaxial ellipsoidal conductor this potential is obtained by using integration along a specific path which is dictated by the geometrical characteristics of the ellipsoidal system as well as by utilizing special properties of ellipsoidal harmonics. The vector potential representation of the magnetic field is also obtained.